Licitações públicas: análise de preços praticados nas licitações do governo do Estado do Espírito Santo - Charpinel, Fabio Paiva (2015)
This research wants to study the bidding process that happens in the Espirito Santo`s Government after the implantation of the Integrated System of Administrative Management (SIGA). A study was made to show the form that the Espirito Santo`s governance has been treating your process of purchases and contracts. After starts of SIGA this study made a review about the biddings to check the efficiency beside the construction of the prices in the process and the winner`s prices. Making a comparison about the prices is possible to conclude that in the global form is still very different the amount established as reference and the amount made by suppliers. So is clear that still exist a great way to come if the Public Administration wants to achieve a better effectiveness in yours bidding process